Interlocking Bricks: Density and Compressive Strength Reduction Due to Addition of Kaolin Clay and RHA - Ibrahim, Norisham; Muhammad Rashidi, Hanna Athirah (International Journal of Integrated Engineering, 2023)
This study investigates the density and compressive strength of interlocking bricks made of mortar added with kaolin clay as cement replacement and RHA for sand replacement. This research also investigated the chemical composition of kaolin clay and RHA used for the interlocking bricks. The mortar used was designed based on the concrete mix proportion of 1:2:3 but removed the coarse aggregate. The water-to-cement ratio utilized was 0.6. Each design mix comprises a combination of kaolin clay and RHA at 5%, 10% and 15% by the total weight of cement and sand, respectively. This paper demonstrates the chemical elements of the kaolin clay and RHA and reports the density and compressive strength of the interlocking bricks compared to control samples. The results indicate that the density and compressive strength of the interlocking bricks decreases as the percentage of kaolin clay and RHA increases. The design mix containing 5% kaolin clay and RHA showed the highest density and compressive strength at 28 days, but the values were smaller than the control mix. In comparison to the control mix, the finding is as follows. At 28 days, the range of density reduction from day 3 for all mixes is between 16 to 25%. Meanwhile, the compressive strength of all mixes decreased by more than 65%, measured in the same duration. The result also showed that silicon dioxide (SiO2) contributes the most significant chemical element in kaolin clay and RHA. Kaolin clay contains almost 65% of SiO2, while RHA holds more than 90% of SiO2.